Product expansions for zeta functions attached to locally symmetric spaces of higher rank - Deitmar, Anton (Duke mathematical journal, 1996)
Duke Mathematical Journal
First available in Project Euclid: 19 February 2004
Elektronische Reproduktion der Druck-Ausgabe 19. Februar 2004
Gesehen am 10.05.2023